THE CHALLENGES IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN TEACHING SPEAKING - Widiantari, Ella; Mandarani, Vidya (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This research aims to analyze and obtain information about teachers' challenges during the implementation of the Merdeka curriculum in teaching English speaking at Muhammadiyah 1 Taman Vocational School and how teachers can overcome these problems. This research method is a qualitative descriptive method and data is obtained through observation and semi-structured interviews. The subject of this research was an 11th-grade English teacher. The results of this study found that the Merdeka Curriculum at Muhammadiyah 1 Taman Vocational School had been implemented and several challenges were found. Teachers believe that the Merdeka curriculum influences students' speaking abilities because teachers can modify teaching methods according to students' needs. Successful implementation of the Merdeka Curriculum can be achieved if teachers can overcome existing challenges. Teacher creativity in teaching, teacher motivation toward students, and institutional support enable teachers to overcome every challenge during the implementation of the Merdeka curriculum in the speaking teaching process.